Internet of agents framework for connected vehicles: A case study on distributed traffic control system - Bui, Khac-Hoai Nam; Jung, Jason J. (Journal of parallel and distributed computing, 2018)
This study focuses on the distributed traffic control system by inspiration of advanced connected vehicle technology. In this regard, we introduce an Internet of Agents (IoA) framework for connected vehicles where agents make their own decisions to improve the effectiveness of the system by connectivity and automatic negotiation with other agents. Specifically, each of the connected vehicles can be regarded as an agent which is able to communicate and collaborate with others based on Vehicle-to-Vehicle (V2V) communication technologies. A case study on distributed traffic control system without traffic signal is presented in this paper. In particular, we consider traffic control at intersection problem as a group mutual exclusion problem where only connected vehicles in non-conflict relationship are able to enter the core of intersection simultaneously. Therefore, we extend the Ricart–Agrawala based-logical clock algorithm to deal with this problem. Various parameters (e.g., number of message exchange, average waiting time, total number of vehicle passing) have been measured to evaluate our approach. The simulated results show that our approach outperforms compared with existing traffic systems and previous works. •A new concept “Internet of Agents” is proposed to support agent collaboration on IoT environments.•We introduce a novel framework for traffic control without traffic signal systems that are not required for self-driving cars.•As a case study, the proposed method has been applied to distributed traffic control.